Analysis of Strategy for Developing Beef Cattle Production on a Smallholder Farming Basis in Musi Banyuasin Regency South Sumatra - Aulia Evi Susanti; Rudy Priyanto -; Muladno - -; Dewi Apri Astuti; Lucia Cyrilla Eko Nugrohowati (Faculty of Animal Science, Universitas Gadjah Mada, 2022)
The increased beef cattle production at traditional farms is a strategy to achieve meat self-sufficiency in 2026. This is accomplished through various parties, including the government, academics, researchers, the private sector, and farmers as the main actors. Therefore, this study aimed to determine and analyze criteria, performance criteria, strategies, and alternatives for sustainable beef cattle production in traditional farms based on the opinion of experts. The research location was School for Smallholder Community (SPR) Maju Bersama, Sungai Lilin Sub-District, Musi Banyuasin Regency, South Sumatra Province, Indonesia. Primary data were collected through FGD (focus group discussion) and interview with expert stakeholders, including farmers, policymakers, entrepreneurs, academics, and research analyst. They were analyzed using the Analytical Hierarchy Process (AHP) with R studio version 4.1.2. The result showed that Musi Banyuasin Regency has a natural resource potential for supporting beef cattle production with an institutional collaborative strategy. The interaction between the production factors showed that the feeding criteria were at the highest level, with 32.05%. Considering the performance criteria, business sustainability was essential at 35.70% and should be achieved by adopting a corporate strategy of 85.52%, implemented through alternative business management at 61.40%.